Effect of oseltamivir phosphate versus placebo on platelet recovery and plasma leakage in adults with dengue and thrombocytopenia; a phase 2, multicenter, double-blind, randomized trial. - Rahajeng N Tunjungputri; Silvita Fitri Riswari; Setyo G Pramudo; Lydia Kuntjoro; Bachti Alisjahbana; Harry Galuh Nugraha; Andre van der Ven; Muhammad Hussein Gasem; Quirijn de Mast (PLoS Neglected Tropical Diseases)
Background Thrombocytopenia, bleeding and plasma leakage are major complications of dengue. Activation of endogenous sialidases with desialylation of platelets and endothelial cells may underlie these complications. We aimed to assess the effects of the neuraminidase inhibitor oseltamivir on platelet recovery and plasma leakage in dengue. Methods We performed a phase 2, double-blind, multicenter, randomized trial in adult dengue patients with thrombocytopenia (<70,000/μl) and a duration of illness ≤ 6 days. Oseltamivir phosphate 75mg BID or placebo were given for a maximum of five days. Primary outcomes were the time to platelet recovery (≥ 100,000/μl) or discharge from hospital and the course of measures of plasma leakage. Results A total of 70 patients were enrolled; the primary outcome could be assessed in 64 patients (31 oseltamivir; 33 placebo). Time to platelet count ≥100,000/μl (n = 55) or discharge (n = 9) were similar in the oseltamivir and placebo group (3.0 days [95% confidence interval, 2.7 to 3.3] vs. 2.9 days [2.5 to 3.3], P = 0.055). The kinetics of platelet count and parameters of plasma leakage (gall bladder thickness, hematocrit, plasma albumin, syndecan-1) were also similar between the groups. Discussion In this trial, adjunctive therapy with oseltamivir phosphate had no effect on platelet recovery or plasma leakage parameters. Trial registration ISRCTN35227717.